Assessment of the Presence of Resistance Genes Detected from the Environment and Selected Food Products in Benin - Dougnon, Victorien; Houssou, Vincentia Marie Camille; ANAGO, Eugénie; Nanoukon, Chimène; Mohammed, Jibril; Agbankpe, Jerrold; Koudokpon, Hornel; Bouraima, Birikissou; Déguénon, Esther; Fabiyi, Kafayath; Hidjo, Marie; Djegui, Fidélia; et al. (My University, 2021)
Gram-negative bacilli can spread from the environment and through food products. (is study aimed to characterize ESBL production and virulence genes from multidrug-resistant Gram-negative bacilli isolated from specimen collected from the environment, kitchen, and food products. A total of 130 samples were collected at local markets in seven different communities in Benin (Abomey-Calavi, Ouidah, Bohicon, Abomey, Parakou, Djougou, and Grand-Popo). Samples were cultured on McConkey and ChromID™ ESBL agar plates. (e isolates were identified by the API 20E gallery. An antibiotic susceptibility test was carried out, and the detection of ESBL production and virulence-associated genes was carried out by Polymerase Chain Reaction (PCR). (e data collected was coded and analyzed using GraphPad prism 7 software and Excel. (e software R was used to calculate the correlation coefficient between the results of the detection of ESBL+ on agar and by the effect of the double synergy. (e results showed that sixty-three (63) bacterial strains were isolated from the 130 samples, of which the dominant species was Chryseomonas luteola (10/63). (e kitchen samples were the most contaminated with 36.50%. More than 40% of the isolates were resistant to at least three different classes of antibiotics. Also, blaSHV gene was detected in 33.33% (21/63) of the isolates and in all isolates of Pseudomonas aeruginosa (5/5%). 11.11% (7/63) of isolates were virulent with dominance of the fimH gene, especially with Escherichia coli (83.33%). (e kitchen samples showed a high prevalence of ESBL-producing strains with fimH gene. (is raises the problem of non-compliance with hygiene rules in community cooking and food handling.
Keywords: multidrug-resistant; ESBL; API 20E gallery; Chryseomonas; luteola; laSHV; Pseudomonas aeruginosa; fimH gene; Escherichia coli